Effect of pilot injection and injection pressure on combustion, performance, exergy and exhaust emission of a bioethanol-diesel fuelled common-rail direct injection engine. (1st April 2022) - Bhowmik, Subrata; Pal, Nirupam; Paul, Abhishek; Panua, Rajsekhar
The present investigation explores the exergy-energy potentials of a CRDI engine fuelled by bioethanol-diesel blends at different pilot fuel mass share, injection pressures and load conditions. Two blends with 5 and 10% bioethanol are chosen for engine testing with 0%, 10% and 20% pilot injection and at 300 bar and 500 bar injection pressure for 50%, 75% and 100% load conditions. The result showed a 6.3% higher brake thermal efficiency, 4.12% lower oxides of nitrogen at 50% load, 5% (by volume) bioethanol blend and with 10% pilot fuel.